The protective effect of rutin on renal ischemia-reperfusion injury - YUAN Zu-jun; ZUO Song; WANG Jia; ZHANG Jiong; FENG Sheng-gang (Linchuang shenzangbing zazhi)
Objective To investigate the effect and mechanism of rutin on renal ischemia-reperfusion injury( IRI). Methods Thirty SD rats were randomly divided into sham operation group( Sham group),renal IRI group( IRI group) and rutin pretreatment group( Rutin group)( n = 10 each). The rat IRI model was constructed by clamping the left renal pedicle and removing the right kidney. The ELISA was used to detect the blood urea nitrogen( BUN),serum creatinine( SCr),tumor necrosis factor alpha( TNFalpha) and interferon gamma( IFN-gamma) and interleukin-8( IL-8). The levels of malondialdehyde(MDA),catalase(CAT),glutathione peroxidase(GPx) and superoxide dismutase( SOD) were determined. The reverse transcriptase polymerase chain reaction was used to detect the expression of TNF-alpha,IFN-gamma and IL-8 mRNA in renal tissues. The pathologic changes of renal tissues were observed by hematoxylin-eosin staining method. Results As compared with the IRI group,the levels of BUN,SCr,TNF-alpha,IFN-gamma,IL-8 and MDA in rutin group were significantly reduced( P < 0. 01),and the activities of CAT,GPx and SOD increased significantly( P < 0. 05). In addition,rutin pretreatment significantly alleviated the pathological changes in renal tissue( P < 0. 05). Conclusions Rutin can attenuate the renal IRI by inhibiting inflammation and oxidative stress.